Data Protection based on Searchable Encryption and Anonymization Techniques - Silveira, Matheus M.; Gomes, Rafael L. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2024: Anais do XXXVII Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2024.2979, 2024)
Data leakage compromises companies’ confidentiality and directly impacts the existing privacy laws, as well as it is necessary to perform a light integration with the legacy systems, in order not to harm the performance of its services. Within this context, this paper presents an innovative cloud system to protect the private data of existing databases (legacy systems of clients) based on Searchable Symmetric Encryption for Databases (SSE-DB) and Permutation and Proprieties Maintenance Anonymization (PPM-Anon), attaching a security solution to the existing databases (without any change in these legacy systems). Results from real experiments using a real cloud environment suggest that the proposed solution is suitable for protecting the data without harming the performance of the existing services.